A Study of the Possible Role of Mesothelium as a Surface for Flowing Blood - Clarke, J M F; Pittilo, R M; Machin, S J; Woolf, N (Thrombosis and Haemostasis, 1984)
Mouse mesothelium has been examined as a surface for supporting blood flow. We have examined ten pieces of intact mesothelium and ten pieces of damaged mesothelium following 10 min exposure to flowing blood in a Baumgartner chamber. Scanning electron microscopy of the intact specimens demonstrated no adhering blood platelets, whereas the damaged specimens were found to be covered with large numbers of adhering platelets. In addition we have demonstrated that undamaged mesothelium does not appear to be morphologically altered after exposure to blood, and that undamaged mesothelium produces significantly more prostacyclin than damaged control. These findings suggest that mesothelial cells hold promise as a lining for prosthetic vascular implants.
Keywords: Mesothelium; Prostacyclin; Scanning electron microscopy; Platelets; Artificial circulation; Vascular prosthesis